Decision Support System for Poor Student Aid Admission Selection (BSM) using the Topsis Method - Siska Liawan (International Journal of Basic and Applied Science, 2019)
The Poor Student Assistance Program (PSAP) is a direct assistance to students and not a scholarship, because it is based on students' economic conditions and not on merit (scholarships). Not all students from poor families can receive the Poor Student Assistance Program (PSAP). So of the many students who are prospective recipients of poor students who have met the criteria for selecting help from poor students, not all of them will be the prospective recipients of these poor students. So that in the selection of prospective beneficiaries of poor students must need a Decision Support System (SPK), so that the school will be helped in determining prospective students who receive Poor Student Assistance (PSAP) so that every student from a poor family can receive such assistance Decision support systems (DSS) are part of a computer-based information system (including knowledge-based systems (knowledge management) that are used to support decision making within an organization or company. poor is Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) TOPSIS provides a solution of a number of possible alternatives by comparing each alternative with the best and the worst alternative alternatives among the alternative problems.